Improvised mask faster recurrent convolutional neural network for breast cancer classification using histopathology images - Pattan M. D. Ali Khan; Xavier Arputha Rathina (Institute of Advanced Engineering and Science, 2026)
Despite the prevalence of this disease, the existing method for obtaining an exact breast cancer diagnosis would need a lot of time and labor. It needs a qualified pathologist to manually process and review histopathological images to distinguish the characteristics that characterize different cancer severity levels. Building a model for automatically detecting, segmenting, and classifying breast lesions using histopathological images seems to be the goal of this work. Various deep learning methods have been used in computational pathology for the diagnosis of cancer. Improved faster recurrent convolutional neural network (IMFRCNN) is a supervised learning system with proposed for recognizing small items like mitotic and non mitotic nuclei. To protect small items from vanishing in the deep layers, this system uses expanded layers in the spine. To close image and the things gap size includes, this approach uses expanded layers. The region proposal network has been created for precise tiny object identification. Researchers examined time for training and testing time for various techniques for identifying objects. The total accuracy of benign/malignant categorization in proposed system reaches 96.5%. The proposed technique offers a thorough and non-invasive method for identifying and categorizes an area of abnormal breast tissue.